Standardization and Optimization of In Vitro Micropropagation Techniques for Mass Multiplication and Restoration of Endangered Wild Brassica Species (International Journal of Environmental Sciences, 2025)
The alarming erosion of wild Brassica germplasm—particularly Brassica tournefortii and Brassica insularis—due to agricultural intensification, habitat degradation, and climate variability, poses a critical challenge to global biodiversity and food security (Maxted et al., 2012; FAO, 2017; IUCN, 2020). These wild species harbor unique allelic variations linked to drought, salinity, and heat tolerance, traits that are becoming increasingly indispensable under the pressures of climate change (Pratap et al., 2021; Razaq et al., 2020). Despite their ecological and genetic value, conservation efforts are hindered by the lack of efficient propagation systems and limited access to viable germplasm in situ. In vitro micropropagation has thus emerged as a powerful alternative, enabling both ex situ conservation and the mass multiplication of elite or endangered genotypes (Pence, 2013; Chauhan et al., 2019).In this study, we aimed to optimize and standardize tissue culture protocols for the large-scale propagation and ecological restoration of B. tournefortii and B. insularis. The workflow encompassed field expeditions for explant and seed collection, GPS-based geotagging for habitat mapping, and controlled lab experiments to determine ideal plant growth regulator (PGR) combinations. For B. tournefortii, shoot regeneration was most efficient on Murashige and Skoog (MS) medium supplemented with 2.0 mg/L benzylaminopurine (BAP) and 0.5 mg/L naphthaleneacetic acid (NAA), yielding a regeneration rate of 78%. Conversely, B. insularis, a more recalcitrant species, showed maximum callus induction (80%) with 2.0 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) (P<0.0001, one-way ANOVA). The treatments were replicated (n=3) and results are presented as means ± SE.Acclimatization under controlled greenhouse conditions demonstrated a survival rate of 92% in B. tournefortii, after which hardened plantlets were reintroduced into two contrasting habitats: a desert fringe (Site A) and a saline depression (Site B). One year post-transplantation, plants at Site A showed 72% survival and 60% flowering, whereas Site B exhibited limited growth and reproductive failure, highlighting the critical role of ecological matching in restoration programs (Munns & Tester, 2008; Sharma et al., 2021).Furthermore, GPS geotagging and GIS mapping allowed for continuous ecological tracking of reintroduced populations, adding a valuable monitoring dimension to conservation science. This integrated approach of micropropagation, ecological validation, and geospatial tracking not only enhances restoration fidelity but also contributes to the preservation of genetic diversity within the Brassicaceae. These findings underline the replicable potential of our optimized protocols for broader conservation efforts, especially for species threatened by similar ecological stressors.In conclusion, this study presents a scientifically validated, ecologically sensitive, and field-tested framework for conserving endangered wild Brassica species. The synergy of biotechnological precision and ecological relevance makes it a model approach for bridging the gap between lab-based conservation and landscape-level restoration.